Evaluating marital stability in late-Victorian Camberwell. (2nd January 2018) - Pimm-Smith, Rachel; Probert, Rebecca
Abstract : What was the extent of marital breakdown and separation in a society where divorce was unlikely to be an option? This article investigates the status and longevity of the marriages of a group of parents whose children were admitted to the care of the poor law authorities in Camberwell in the latter part of the nineteenth century. It finds that spousal death or misfortune, rather than marital breakdown, were the primary reasons for a parent to send a child to the poor law authorities, and that most of the marriages of the parents in the sample remained intact. It also explores whether those who separated formed new co-residential relationships.